Design editorial de livro de receitas para pessoas com intolerância a glúten - Piper, Waline (2017)
This work presents the theoretical basis and methodology chosen for the development of the book "It does not contain gluten, but it is delicious", with the purpose of taking recipes without gluten to the group of people who cannot or did choose not to ingest this protein. For the project, the principles of editorial design are used to design and delivering the information to the reader in the most intelligible possible way. It is estimated that 1% of the world population is gluten intolerant, and the gluten-free long life diet is the only treatment available until today. It was approached all the main areas in the design of the cookbook, such as: photography, illustration, diagramming for the generation of alternative graphic products.